The Effect of Problem-Based Learning within Socioscientific Contexts on Students’ Scientific Literacy and Argumentation Skills - Ade Putri Purnamasari; Ketut Suma; Ni Ketut Rapi (Postgraduate, University of Mataram, 2025)
Scientific argumentation is a critical cognitive and social skill that enables students to evaluate claims, assess evidence, and communicate reasoning logically—skills central to scientific literacy. The main objective of this study is to compare the effectiveness of the PBL-SSI vs. PBL model on improving students' Scientific Literacy and Scientific Argumentation Skills. This type of research is a quasi-research with a pre-test post-test non-equivalent control group design. The study population was all 233 students of grade VII of SMP Negeri 1 Sidemen in the 2024/2025 academic year. Based on the analysis, the results found: there are differences in scientific literacy and scientific argumentation skills of students who learn using problem-based learning models in the context of socio-scientific issues with problem-based learning models (F = 2.44; p < 0.05), there are differences in scientific literacy who learn using problem-based learning models in the context of socio-scientific issues with problem-based learning models. (F = 56.96; p < 0.05), there is a difference in the scientific argumentation ability of students who learn using a problem-based learning model in the context of socio-scientific issues with a problem-based learning model (F = 39.86; p < 0.05). There is a positive influence of 97% on the problem-based learning model in the context of socio-scientific issues on improving students' scientific literacy and scientific argumentation abilities.